Do SNAP work requirements work? - Timothy F. Harris (W.E. Upjohn Institute for Employment Research, 2019)
The American Recovery and Reinvestment Act waived Supplemental Nutrition Assistance Program (SNAP) work requirements nationally in 2010 and broadened the eligibility for receiving waivers in subsequent years for Able-Bodied Adults without Dependents (ABAWD). From 2011 to 2016, many states voluntarily imposed work requirements, while other areas became ineligible for waivers because of improved economic conditions. Did the work requirements increase employment as intended, or did the policy merely remove food assistance for ABAWD who - despite an improving economy - still could not find employment? Using data from the American Community Survey from 2010 to 2016, I analyze the influence of work requirements on employment and SNAP participation for ABAWD. I find that work requirements significantly decreased SNAP participation and marginally increased employment for ABAWD using Difference-in-Difference-in-Differences estimation. This study contributes to the current policy debates on the effectiveness of expanding or instituting work requirements for welfare programs.
Keywords: J21; J68; H42; H75; 330; Supplemental Nutrition Assistance Program; SNAP; Food Stamps; work requirements; eligibility; employment